Low-frequency behaviour of a sound field inside a reverberant room: Measurements and numerical prediction tools. Issue 2 (June 2019) - Negreira, Juan; Sjöström, Anders; Glebe, Dag
The low-frequency properties of a room (where statistical methods in the standards cannot be applied directly) are often hard to estimate due to strong modal behaviour. The situation gets complicated by the fact that variations in the furnishing can have an impact on the modal patterns and therefore can also influence the results of measurements at certain points, in spite of the room properties being the same. The latter can hinder the achievement of acoustic comfort in dwellings, even if they comply with the current regulations, especially due to the fact that low-frequency noise is left outside the scope, since the standards currently in force do not require measurements below 100 Hz (albeit Sweden set 50 Hz as lower limit). This article aims to study variations of the sound field that results of varying the position of three moderately absorbing boards, which emulate how very sparse furniture can impact the sound field when relocated in the room. Furthermore, the potential of numerical models as prediction tools for such problems is pointed out.